Application of Biogas Slurry in Combination with Chemical Fertilizer Enhances Grain Yield and Profitability of Maize (Zea Mays L.). Issue 19 (27th October 2020) - Ferdous, Zannatul; Ullah, Hayat; Datta, Avishek; Attia, Ahmed; Rakshit, Amitava; Molla, Samim Hossain
ABSTRACT: Biogas slurry is a by-product of biogas production, which is generated from anaerobic digestion of animal waste and crop residue. It is generally considered a waste material. However, its application can improve soil health, crop yield, and profitability of the farmers as it is a rich source of organic matter and plant nutrients. Field experiments were conducted to evaluate the combined effect of biogas slurry and chemical fertilizer on grain yield of maize and economic return. The treatments were soil test-based chemical fertilizer, chemical fertilizer + cow dung manure (5 t h –1 ) or poultry manure (3 t h –1 ), chemical fertilizer + cow dung biogas slurry (5 t h –1 ) or poultry biogas slurry (3 t h –1 ) along with traditional farmer practice as the control. Application of biogas slurry from cow dung or poultry manure in combination with chemical fertilizer resulted in 20–24% higher grain yield along with 22–23% greater gross return and 52–53% more gross margin compared with the traditional farmer practice indicating the beneficial effect of integrated application of biogas slurry and chemical fertilizer on maize productivity and financial return. Integrated application of biogas slurry and chemical fertilizer has a good potential in maize production as it provides higher grain yield and economic profitability.